Pre-determined fixed fare structure for rickshaws to integrate with mass transit systems. Issue 1 (March 2020) - Rahman, M. Shafiq-Ur; Timms, Paul
Abstract: This paper examines the feasibility of pre-determined fare structures for rickshaws. An empirical study was conducted with two case study locations (prospective BRT stations) in Dhaka City, Bangladesh. Eleven focus group discussions (FGDs) were held with rickshaw-pullers and other stakeholder groups, and semi-structured open-ended interviews were conducted with twenty five transport professionals/policymakers. It was found that rickshaw-pullers often like a bargaining process for fixing a fare so that they can charge more from passengers, particularly from those who are new in the area or 'seem to be' wealthy, or when there is no other alternative mode available for passengers. On the other hand, passengers prefer a fixed fare structure and do not like the bargaining process. Rickshaw-pullers, passengers and policymakers all mentioned that it would be possible to have a pre-determined fixed fare structure for rickshaws if rickshaws were more localised (serving only within a particular neighbourhood or for a short distance, as an access leg to public transport). However, this policy would need to be backed by effective planning, regular monitoring and enforcement, along with 'awareness generation' for rickshaw-pullers and wide scale publicity campaigns.